Research on a remote non-real-time closed-loop testing technique for safety and stability control systems - ZHAO Wei; HOU Yuqiang; CHEN Xiong; XUE Feng; XU Jianbing (Zhejiang dianli, 2024)
At present， safety stability control system inspection primarily relies on independent in-plant testing， laboratory experiment and on-site joint testing， making it difficult to completely eliminate potential risks in safety and stability control systems. To address the shortcomings of existing testing methods， a remote non-real-time closed-loop testing technique for safety and stability control systems is proposed. By integrating key technologies such as hardware-in-the-loop simulation， 5G communication networking， wide-area synchronous triggering， and multi-communication protocol conversion， key modules， including the platform management system， testing master station and testing terminals， have been developed， and a remote non-real-time closed-loop testing process has been formulated. Taking the safety and stability control system for hydropower transmitted via ultra-high-voltage direct current in Sichuan power grid as an example， the feasibility of the proposed technique is validated.